'Real-world' haemorrhagic rates for warfarin and dabigatran using population-level data in New Zealand. (15th January 2016) - Nishtala, Prasad S.; Gnjidic, Danijela; Jamieson, Hamish A.; Hanger, H. Carl; Kaluarachchi, Chanaka; Hilmer, Sarah N.
Abstract: Background: Anticoagulants such as warfarin and dabigatran can significantly reduce the risk of stroke in individuals with atrial fibrillation that may lead to increased risk of bleeding, especially in older people. Evidence for bleeding risks with anticoagulants within the context of doses, multimorbidity and impaired renal function in real world setting is lacking. Therefore we aimed to assess and compare real world bleeding risks with warfarin and dabigatran. Secondary analyses involved examining risk of fatal haemorrhages. Methods and results: We formed two inception cohorts of propensity score (PS) matched older patients (≥ 65 years), who initiated dabigatran or warfarin between July 2011 and December 2012. A total of 4835 dabigatran users were matched to 4385 warfarin users in dose independent binary PS matching. A dose dependent PS matching resulted in 2383 warfarin, 2153 dabigatran 150 mg and 3395 dabigatran 110 mg users. In the first cohort, compared to warfarin, the hazard ratios (95% confidence intervals) for dabigatran were 0.45 (0.37–0.55) for any haemorrhage; 1.16 (0.87–1.56) for gastrointestinal haemorrhage; and 0.29 (0.09–0.86) for intracerebral haemorrhage. Similar associations were observed in the first 30 days of treatment. In dose dependent matched cohort, the risk of any haemorrhage was lower in individuals receiving dabigatran 110 mg (HR; 95% CI: 0.40 (0.31–0.52)) and 150 mg (HR; 95% CI: 0.29 (0.19–0.41)) compared to warfarin. Conclusions: The risk of any haemorrhage and intracerebral haemorrhage was lower in dabigatran users compared to warfarin users. Importantly no increased risk of gastrointestinal haemorrhage was found in dabigatran users. The incidence rates for any haemorrhage were found to be higher in first 30 days of any anticoagulant treatment, but hazard ratios remained similar during the study period.